2016
DOI: 10.1177/2156587215607673
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Traditional Medicines in India

Abstract: For the first time, we have a comprehensive database on usage of AYUSH (acronym for Ayurveda, naturopathy and Yoga, Unani, Siddha, and Homeopathy) in India at the household level. This article aims at exploring the spread of the traditional medical systems in India and the perceptions of people on the access and effectiveness of these medical systems using this database. The article uses the unit level data purchased from the National Sample Survey Organization, New Delhi. Household is the basic unit of survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…The respondents later asked question regarding the use of Unani medicine as a better healthcare option, out of 480, majority 444 (92.5%) of them responded positively by giving reasons that it has no or negligible side effects (69.82%), effective (9.23%), affordable (11.04%), being convenient palatable (5.63%) and cure diseases from its root (4.28%). 5,7 These findings are comparable with another study in which 62.8 % respondents thought it has no side effects, 8 but in terms of affordability which came out to be (11.04%) in present study is much less in contrast to many other study findings done previously on traditional medicine in Nigeria, Ethiopia. [11][12][13] A study from Dhaka observed that people are turning to Unani due to serious side effects of modern medicine and lack of effectiveness in many of the chronic disorders.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The respondents later asked question regarding the use of Unani medicine as a better healthcare option, out of 480, majority 444 (92.5%) of them responded positively by giving reasons that it has no or negligible side effects (69.82%), effective (9.23%), affordable (11.04%), being convenient palatable (5.63%) and cure diseases from its root (4.28%). 5,7 These findings are comparable with another study in which 62.8 % respondents thought it has no side effects, 8 but in terms of affordability which came out to be (11.04%) in present study is much less in contrast to many other study findings done previously on traditional medicine in Nigeria, Ethiopia. [11][12][13] A study from Dhaka observed that people are turning to Unani due to serious side effects of modern medicine and lack of effectiveness in many of the chronic disorders.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with many other studies done earlier. [4][5][6] The usage of AYUSH across country varies; it was reported to be 32.1% in Andhra Pradesh according to the National Sample Survey Organization database by Srinivasan et al 7 The awareness level of respondents in the present study was very good which is in consistent with the study done in Dhaka but the majority of the respondents were from a particular sect of religion who are generally inclined towards Unani medicine. 4 However, less usage of Unani medicine among half of the respondents in present study was attributed to lack of knowledge, perception that it is slow acting so can't be used in emergency conditions, accessibility issues and for some people lack of scientific basis.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the present study, awareness level of respondents was very good, almost all patients knew about Unani Medicine (UM) and friends, family members and colleagues were the common source of information of UM which is consistent with previous studies. [3][4][5][6][7] The study conducted by National Sample Survey Organization's Report covering all parts of Indian subcontinent, less than 30% of the respondents have reported use of AYUSH medicines. 6 Therefore, there is need to improve the awareness about the AYUSH systems.…”
Section: Discussionmentioning
confidence: 99%